A Self-Adaptive Technique for Solving Variational Inequalities: A New Approach to the Problem - Muhammad Bux; Saleem Ullah; Muhammad Shoaib Arif; Kamaleldin Abodayeh (Journal of Function Spaces)
Variational inequalities are considered the most significant field in applied mathematics and optimization because of their massive and vast applications. The current study proposed a novel iterative scheme developed through a fixed-point scheme and formulation for solving variational inequalities. Modification is done by using the self-adaptive technique that provides the basis for predicting a new predictor-corrector self-adaptive for solving nonlinear variational inequalities. The motivation of the presented study is to provide a meaningful extension to existing knowledge through convergence at mild conditions. The numerical interpretation provided a significant boost to the results.